A closer look at the role of healthcare in the recent mortality decline in the Netherlands: results of a record linkage study. Issue 6 (22nd January 2015) - Peters, F; Nusselder, W J; Mackenbach, J P
Abstract : Background: Since 2002, Dutch mortality rates decreased rapidly after decades of stagnation. On the basis of indirect evidence, previous research has suggested that this decline was due to a sudden expansion of healthcare. We tested two corollaries of this hypothesis—first, that the decline was concentrated among those with ill-health and second, that the decline can be statistically accounted for by increases in healthcare utilisation. Methods: We linked the Dutch health interview survey to the mortality register and constructed two cohorts, consisting of 7691 persons interviewed in 2001/2002 and 8362 persons interviewed in 2007/2008, each with a 5-year mortality follow-up (659 deaths in total). The change in mortality between both cohorts was computed using Cox proportional hazard models. We estimated the change in mortality by severity of chronic conditions and with respect to the inclusion of indicators of healthcare utilisation. Results: Between the two study cohorts, mortality declined by 15% (95% CI 2% to 29%), and mortality reduction was greatest for those suffering from fatal and non-fatal conditions with a decline of 58% (95% CI 35% to 78%). Even after adjustment for health status and risk factors, most indicators of healthcare utilisation were associated with higher instead of lower mortality and changes in healthcare utilisation did not explain the decline in mortality. Conclusions: Our results only partly confirm the hypothesis that an expansion of healthcare explains the recent mortality decline in the Netherlands. Owing to confounding by health status, it is difficult to reproduce the mortality-lowering effects of healthcare utilisation of individual level studies in the open population.